Matching the mandate and resource envelope. - GREENIDGE, Carl B. (1997)
Discusses the core issue that governments of the Caribbean and most of the world have had to face over the past decade - how to settle on a mandate for the public sector, commensurate with what taxes the electorate will pay. Points out that while this is often portrayed as an economic exercise, it is first and foremost a political issue.